Amphioxus Gli knockout disrupts the development of left–right asymmetry but has limited impact on neural patterning - Huang, X; Ren, Q; Wang, Y; Shimeld, S; Li, G (Springer, 2023)
The Gli transcription factors are the primary mediators of Hedgehog (Hh) signaling. Vertebrate genomes contain multiple Gli paralogues with different functions downstream of Hh signal receipt, in part explaining the complexity of cellular responses to Hh that allow concentration-dependent target gene activation. Amphioxus is a chordate that split from the vertebrate lineage early in the evolution of chordates, before the genome duplications that occurred in early vertebrate evolution. It has a single Gli gene whose transcripts can be alternately spliced to yield two protein isoforms called GliS and GliL. We generated two knockout mutations in amphioxus Gli, one that affects the whole gene and a second that only affects GliL. Both knockouts showed major morphological and molecular defects in the development of left–right asymmetry, a phenotype that is similar but not identical to that previously found in Hh mutants. Hh signaling also patterns the amphioxus neural tube. Here, however, knockout of GliL showed no identifiable phenotype, while knockout of the full gene showed only small changes to the expression of one gene family, Olig. Other genes that were prominently affected by Hh knockout were not altered in expression in either knockout. Reasons for the differences between Hh and Gli knockouts in the pharynx and neural tube are discussed in the context of the likely different functions of amphioxus Gli isoforms.